2020
DOI: 10.1186/s13195-020-00659-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing what matters most to patients with or at risk for Alzheimer’s and care partners: a qualitative study evaluating symptoms, impacts, and outcomes

Abstract: Background The What Matters Most (WMM) study was initiated to evaluate symptoms, AD-related impacts, treatment-related needs, preferences, and priorities among individuals with or at risk for Alzheimer’s disease (AD) and their care partners. The objective of this qualitative study phase was to identify a comprehensive set of concepts of interest that are meaningful to individuals across the AD continuum. Methods Interviews were conducted with 60 clinically referred indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 10 publications
1
52
0
Order By: Relevance
“…Different studies have shown that persons with AD are still able to describe their problems, experiences, and preferences at different stages of the disease [ 10 , 14 , 15 ]. In a qualitative and quantitative study with mild and moderate AD persons, Trindade et al found that awareness of condition was more preserved than awareness of specific functional deficits [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies have shown that persons with AD are still able to describe their problems, experiences, and preferences at different stages of the disease [ 10 , 14 , 15 ]. In a qualitative and quantitative study with mild and moderate AD persons, Trindade et al found that awareness of condition was more preserved than awareness of specific functional deficits [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…AD care should focus on person-centered outcomes [ 14 , 15 ]. Maintaining autonomy and quality of life based on persons’ preferences and beliefs is essential, especially in the early stage of the disease when decision-making capacity is less impaired [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes that we did not replicate are eating behaviors, apathy, and self‐efficacy in the ability to manage memory impairment. In addition, a recent qualitative study examined what matters most to patients and care partners across the AD continuum, by means of interviews only 25 . They also observed that memory (e.g., forgetting friends/family) was reported as one of the most challenging issues by the majority of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The Alzheimer's Association reports that twice as many caregivers of those with dementia compared with caregivers of people without dementia indicate substantial emotional and physical difficulties (18). In fact, 66.7 percent of caregivers evaluated in the What Matters Most (WMM) study reported that their physical health had suffered (25). Caregivers of people with dementia also have a higher prevalence of anxiety and depression (anxiety: 44%, depression: 30–40%) compared with caregivers of individuals with stroke (anxiety: 31%, depression: 19%) (18).…”
Section: The Impact Of Ad On Caregivers: Burden and Family Spilloversmentioning
confidence: 99%